Prevalence and Sensitivity Pattern of MRSA against Gentamycin, Vancomycin & Ciprofloxacin, in Indoor and OPD Patients of Holy Family Hospital - Furqan Ali Taj, Furqan Ali Taj; Faisal Javed , Faisal Javed; Muhammad Soban Saeed, Muhammad Soban Saeed; Sofia Khan, Sofia Khan; Behzad Masood, Behzad Masood; Afzaal Aleem Khan, Afzaal Aleem Khan; Muhammad Usman, Muhammad Usman; Rabi Zubair, Rabi Zubair; Muhammad Umair, Muhammad Umair; Muhammad Omer Farooq Khan, Muhammad Omer Farooq Khan (Students' Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Methicillin resistant Staphylococcus aureus (MRSA) is a common pathogen which has increased both morbidity and mortality in hospitals and out-door patients. Objective: Aim of our study is to measure prevalence of MRSA in in-door patients and out- door patients, as well as its sensitivity against gentamycin, vancomycin and ciprofloxacin. Methods: A sample of 194 S. aureus was taken retrospectively from Pathology lab of a tertiary care hospital. MRSA was identified and further subjected against gentamycin, vancomycin and ciprofloxacin. Result: 65.9% of S. aureus isolates were MRSA. 22.7%, 35.7%, 99.1% of MRSA were susceptible to ciprofloxacin, gentamycin and vancomycin, respectively. 75.8% MRSA was from pus samples. 66% MRSA was from in-door patient department (IPD). Conclusion: MRSA was more prevalent in IPD. MRSA prevalence is escalating. Vancomycin is losing its effectiveness against MRSA as one resistant case was found. Inappropriate use and unprofessional prescriptions for antibiotics can be the main cause. Proper legislative action is required to keep in control the prescriptions for antibiotics. Keywords: Methicillin-Resistant Staphylococcus aureus, Bacterial drug resistance, Antimicrobial drugs